Transcriptional regulation of MdmiR285N microRNA in apple (Malus x domestica) and the heterologous plant system Arabidopsis thaliana. (1st July 2020) - Pompili, Valerio; Piazza, Stefano; Li, Mingai; Varotto, Claudio; Malnoy, Mickael
Abstract: Malus x domestica microRNA MdmiR285N is a potential key regulator of plant immunity, as it has been predicted to target 35 RNA transcripts coding for different disease resistance proteins involved in plant defense to pathogens. In this study, the promoter region of MdmiR285N was isolated from the apple genome and analyzed in silico to detect potential regulatory regions controlling its transcription. A complex network of putative regulatory elements involved in plant growth and development, and in response to different hormones and stress conditions, was identified. Activity of the β-Glucoronidase ( GUS ) reporter gene driven by the promoter of MdmiR285N was examined in transgenic apple, demonstrating that MdmiR285N was expressed during the vegetative growth phase. Similarly, in transgenic Arabidopsis thaliana, spatial and temporal patterns of GUS expression revealed that MdmiR285N was differentially regulated during seed germination, vegetative phase change, and reproductive development. To elucidate the role of MdmiR285N in plant immunity, MdmiR285N expression in wild-type apple plants and GUS activity in transgenic apple and Arabidopsis thaliana plants were monitored in response to Erwinia amylovora and Pseudomonas syringae pv. Tomato DC3000. A significant decrease of MdmiR285N levels and GUS expression was observed during host-pathogen infections. Overall, these data suggest that MdmiR285N is involved in the biotic stress response, plant growth, and reproductive development.